Heavy Chain Disease with Cystic Lung Disease Presenting as Recurrent Spontaneous Pneumothorax in a Young Adult - Dodos, Konstantinos; Kalamara, Tsampika Vasileia; Georgakopoulou, Vasiliki Epameinondas (Acta medica Lituanica, 2025)
Heavy chain diseases (HCDs) are rare B-cell/plasma cell disorders characterized by secretion of truncated immunoglobulin heavy chains without light chains. Pulmonary involvement has been described but is typically limited to interstitial or infiltrative patterns; whereas, cystic lung disease is exceptionally rare. We report a 23-year-old previously healthy male who presented with recurrent spontaneous pneumothoraces over a two-year period. High-resolution computed tomography revealed numerous bilateral thin-walled cysts with upper-lobe predominance, with several of these abutting the pleural surface. Laboratory evaluation demonstrated a discrete monoclonal spike on serum protein electrophoresis, and immunofixation confirmed an isolated IgG heavy chain without light chains, consistent with γ-heavy chain disease (γ-HCD). Bone marrow biopsy showed a mild increase in plasma cells (5–10%) without overt malignancy, and alternative causes of cystic lung disease, including Birt-Hogg-Dubé syndrome, autoimmune disease, α1-antitrypsin deficiency, and HIV, were excluded. This case highlights γ-HCD as a rare cause of diffuse cystic lung disease with recurrent pneumothorax, expanding the pulmonary spectrum of heavy-chain dyscrasias. The radiographic overlap with light-chain deposition disease emphasizes the need to include monoclonal gammopathies in the differential diagnosis of unexplained cystic lung disease. Recognition of γ-HCD in this context is clinically important, as it may precede lymphoproliferative malignancy and mandates careful longitudinal surveillance.